Towards Precision Medicine with Genomics using Big Data Analytics - Badugu Sobhanbabu; K.F. Bharati (International Journal of Computational and Experimental Science and Engineering, 2025)
Precision medicine is considered to be the future of healthcare. It allows doctors to select treatments based on the patient’s genetic information. Precision medicine is being adapted to a few typical complicated treatments like cancer at an intermediate level. As genetic information is in large volumes, Big data analytics showing a reliable promise of the modern-day health care revolution. Extremely large and continuous collection of large volumes of data like Genomics, Proteomics, Glycomics etc. is creating a challenge in analysis and interpretation, which is addressed effectively by the Big data analytics. This research work reviews and highlights the evolution of Precision medicine, Big Data Analytics and its significance in Precision medicine and related work. Also detailed the Machine learning perspectives on the Precise medicine with genomic data models along with Challenges.